2018
DOI: 10.1515/jpem-2017-0391
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in childhood: old lessons and current challenges

Abstract: Hypovitaminosis D in childhood is a re-emerging public health problem in developed countries. New life style habits, current "epidemics" of obesity in children and adolescents worldwide, and other preventable risk factors may play a role in favoring the occurrence of vitamin D deficiency. In addition to skeletal consequences, hypovitaminosis D has been found to be involved in the development of serious health extra-skeletal problems in childhood, including atopy and autoimmunity. The increasing concerns about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
137
0
22

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(162 citation statements)
references
References 117 publications
3
137
0
22
Order By: Relevance
“…Epidemiological studies have shown that it can lead to rickets in children and osteomalacia in adults and may play a role in a variety of extraskeletal disorders, including asthma, type 1 diabetes, infectious and cardiovascular diseases and cancer. 3,4 The current epidemic of obesity is a challenging public health issue worldwide, 5 (35.3%) had vitamin D deficiency, defined as 10-20 ng/mL, and two (2.9%) had a severe vitamin D deficiency of less than 10 ng/ mL. 2 Other risk factors for vitamin D deficiency include adiposity and female gender.…”
Section: Family-related Factors May Affect Serum Vitamin D Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies have shown that it can lead to rickets in children and osteomalacia in adults and may play a role in a variety of extraskeletal disorders, including asthma, type 1 diabetes, infectious and cardiovascular diseases and cancer. 3,4 The current epidemic of obesity is a challenging public health issue worldwide, 5 (35.3%) had vitamin D deficiency, defined as 10-20 ng/mL, and two (2.9%) had a severe vitamin D deficiency of less than 10 ng/ mL. 2 Other risk factors for vitamin D deficiency include adiposity and female gender.…”
Section: Family-related Factors May Affect Serum Vitamin D Levelsmentioning
confidence: 99%
“…2 Other risk factors for vitamin D deficiency include adiposity and female gender. 3,4 The current epidemic of obesity is a challenging public health issue worldwide, 5 and a number of factors may contribute to vitamin D deficiencies in obese children. These include sedentary lifestyles, the prevalence of indoor activities, with resulting decreased sun exposure, and vitamin D sequestration into adipose tissue.…”
Section: Family-related Factors May Affect Serum Vitamin D Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity‐related consequences, such as type 2 diabetes, cardiovascular disorders and death, have been associated with low vitamin D in adults. However, it is unclear whether vitamin D plays a direct role in glucose metabolism or whether there is an association without direct causality …”
Section: Clinical Characteristics Divided Into Vitamin D Deficiency Amentioning
confidence: 99%
“…However, it is unclear whether vitamin D plays a direct role in glucose metabolism or whether there is an association without direct causality. 1 Longitudinal studies of vitamin D and prediabetes are scarce in children with obesity, and intervention studies in adults have had different follow-up periods. 2 Our original cross-sectional study of children aged 4.5-17.9 years from January 2011 to January 2014 showed that vitamin D deficiency was associated with IFG in children with obesity.…”
mentioning
confidence: 99%